ANKYLOSED SCOLIOTIC FETUS IN A CROSSBRED HEIFER - SHARMA, U; KUMAR, s; KUMAR, S (The Indian Journal of Animal Reproduction, 2016)
Successful vaginal delivery of a fetus with arthrogryposis and scoliosis by mutations without any post-operative complication was recorded in a crossbred cattle heifer.